A Croce reader : aesthetics, philosophy, history, and literary criticism - Croce, Benedetto, 1866-1952. (Toronto ; Buffalo ; London : University of Toronto Press, 2017)
"Benedetto Croce was a historian, humanist, political figure, and the foremost Italian philosopher of the early twentieth-century. A Croce Reader brings together the author's most important works across the fields of aesthetics, philosophy, history, literary criticism, and the Baroque and presents the "other" Croce that has been erased by scholarly tradition, including by Croce himself. Massimo Verdicchio traces the progress of Croce as a thinker, focusing on his philosophy of absolute historicism and its aesthetic implications. Unlike other anthologies, A Croce Reader includes essays from the Aesthetics of 1902 and key studies on Vico, Hegel, and Pirandello. Verdicchio's masterful translation of the source material welcomes specialists and non-specialists alike to discover the "other" Croce for themselves."--
Aesthetics -- Philosophy -- History -- Literary criticism -- The baroque.
Translated from the Italian.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Croce, Benedetto, -- 1866-1952.; Croce, Benedetto, -- 1866-1952; PHILOSOPHY -- History & Surveys -- Modern; LITERARY CRITICISM -- European -- Italian; Essay; essays; Essays; Essays; Essais